Respuesta :
answer is D. y – 2 = 4(x + 1)
not an equation of the line going through (3, 6) and (1, –2)?
...............................................
not an equation of the line going through (3, 6) and (1, –2)?
...............................................
To solve this, find your slope-intercept equation, then convert to point-slope. y=mx+b, m=(y2-y1)/(x2-x1)=(6+2)/(3-1)=4, y=4x+b, b=y-4x=6-4(3)=-6, y=4x-6. This eliminates A. Next, convert to point-slope, y-y1=m(x-x1), This gives you y-y1=4(x-x1). Using your two points, you can get y-6=4(x-3) and y+2=4(x-1) as possible equations, which eliminates B and C, meaning your answer is D.